The Tale of the Argonauts - Apollonius, Rhodius; Gollancz, Israel, 1864-1930; Way, Arthur S. (Arthur Sanders), 1847-1930 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Tale of the Argonauts" by Rhodius Apollonius is a Greek epic poem written in the 3rd century BC. It tells the myth of Jason and the Argonauts as they voyage to remote Colchis to retrieve the Golden Fleece. Their heroic adventures intertwine with Jason's relationship with Medea, a Colchian princess and sorceress. The poem incorporates scholarly research in geography, ethnography, and religion, while pioneering the exploration of romantic love in epic poetry. This influential work helped shape the romance novel genre and profoundly impacted later Latin poets. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Argonautica
Release date is 2021-01-08
David Thomas
Keywords: Jason -- (Mythological character) -- Poetry; Medea, consort of Aegeus, King of Athens (Mythological character) -- Poetry; Argonauts (Greek mythology) -- Poetry